Comparative analysis of MEMS piezoelectric cantilever beam for energy harvesting application based on mechanical vibrations - S, Bestley Joe; S, Maflin Shaby; S, Rajasekaran (International Journal of Engineering and Technology, 2018)
One of the significant application of microelectromechanical systems is energy harvesting. In recent years cantilever beam based on pie-zoelectric materials have garnered paramount interest for mechanical vibration to electric energy conversion. Research work are being carried out to harness maximum amount of power out of vibrations. This research work is based on the design and simulation of cantilever beamwith eight different piezo-materials for energy harvesting from ambient vibrations and comparison of observed parameters. This cantilever beam consist of fixed end made of stainless steel, a movable end with piezo-material, a proof mass at the movable end. Simulations were performed using COMSOL multiphysics software. In the analysis, specific load, acceleration and dimensions were considered and simula-tion was done for five different characteristic features like stress distribution, surface potential distribution, frequency response, acceleration dependence and load dependence. Barium Titanate gave a maximum surface potential of 2.75V at hinges. Quartz, barium titanate both gave equal and maximum power output of 5.3mW.